Pengaruh Keputusan Investasi, Kebijakan Dividen, Dan Kebijakan Hutang Terhadap Nilai Perusahaan Sektor Property, Real Estate Dan Building Contructions Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016-2018 - Mardiyani, Rosi Esa; Rukmana, Heru Satria (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2021)
This study aims to determine the effect of investment decisions, dividend policy and debt policy on corporate value decisions in the property, real estate and building construction sectors for the period 2016-2018. This research uses quantitative analysis. The sample collection method used was purposive sampling, namely property, real estate and building construction sector companies listed on the Indonesia Stock Exchange in a row for the period 2016-2018. The data collection technique uses documentary data, namely in the form of previous research journals, literature and financial reports. The data analysis technique used correlation coefficient test, determination coefficient test, partial t statistical test, f statistical test and multiple linear regression analysis. The coefficient of determination test results where the adjusted rsquare value of the Investment Decision variable (X1), the Dividend Policy variable (X2) and the Debt Policy variable (X3) is 90.5%, which means that the deterimination coefficient value of the Investment Decision variable (X1), the Dividend Policy variable (X2) ) and the debt policy variable (X3) has a dominant factor affecting the firm value variable (Y). Performing the classical assumption test shows that the data in this study show positive results for conducting multiple regression tests. Based on the results of multiple linear regression, the equation ¶ = -1.972 + 0.071 + 0.018 + 0.602 is obtained. From the results of hypothesis testing, it states that there is an influence of the Investment Decision (X1), Dividend Policy (X2) and Debt Policy (X3) on Firm Value (Y). The results of the partial t test where the significant value of the Investment Decision variable (X1) is 0.000 <0.05, the significant value of the Dividend Policy variable (X2) is 0.000 <0.05 and the significant value of the Debt Policy variable (X3) is 0.022 <0.05.